2014
DOI: 10.1002/chem.201402559
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Cycloadditions of 1‐Haloalkynes with Nitrile Oxides and Organic Azides: Synthesis of 4‐Haloisoxazoles and 5‐Halotriazoles

Abstract: (Cyclopentadienyl)(cyclooctadiene) ruthenium(II) chloride [CpRuCl(cod)] catalyzes the reaction between nitrile oxides and electronically deficient 1-choro-, 1-bromo- and 1-iodoalkynes leading to 4-haloisoxazoles. Organic azides are also suitable 1,3-dipoles, resulting in 5-halo-1,2,3-triazoles. These air tolerant reactions can be performed at room temperature with 1.25 equiv of the respective 1,3-dipole relative to the alkyne component. Reactive 1-haloalkynes include propiolic amides, esters, ketones and phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 112 publications
(88 reference statements)
0
72
0
Order By: Relevance
“…Among all the Ru catalysts, the most investigated ones are the pentamethylcyclopentadienyl ruthenium chloride-based (noted [Cp*RuCl]) complexes), although Fokin's group also observed that the steric encumbrance imparted by the Cp* ligand is detrimental to the reaction [81]. These complexes catalyzed the regioselective RuAAC reaction of terminal alkynes forming, unlike CuAAC catalysts, 1,5-disubstituted 1,2,3-triazoles, and also unlike the CuAAC catalysts, they reacted with internal alkynes providing trisubstituted 1,2,3-triazoles [28,39,40,82].…”
Section: The Ruaac Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the Ru catalysts, the most investigated ones are the pentamethylcyclopentadienyl ruthenium chloride-based (noted [Cp*RuCl]) complexes), although Fokin's group also observed that the steric encumbrance imparted by the Cp* ligand is detrimental to the reaction [81]. These complexes catalyzed the regioselective RuAAC reaction of terminal alkynes forming, unlike CuAAC catalysts, 1,5-disubstituted 1,2,3-triazoles, and also unlike the CuAAC catalysts, they reacted with internal alkynes providing trisubstituted 1,2,3-triazoles [28,39,40,82].…”
Section: The Ruaac Reactionsmentioning
confidence: 99%
“…These complexes catalyzed the regioselective RuAAC reaction of terminal alkynes forming, unlike CuAAC catalysts, 1,5-disubstituted 1,2,3-triazoles, and also unlike the CuAAC catalysts, they reacted with internal alkynes providing trisubstituted 1,2,3-triazoles [28,39,40,82]. The Cp*RuCl based catalysts provided multiple application that were recently developed (vide infra) [81,[83][84][85][86][87]. M a n u s c r i p t The first mechanistic investigation was proposed by Lin, Jia, Fokin and coworkers based on DFT calculations [39].…”
Section: The Ruaac Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reactions were carried out using freshly distilled and dry solvents. Parent N,N‐dipropylpropiolamide was prepared according to published procedures …”
Section: Methodsmentioning
confidence: 99%
“…Compound 4 has however been used extensively in [3+2]-cycloadditions with organic azides. [17][18][19][20] …”
mentioning
confidence: 99%